1998
DOI: 10.1021/ie9707578
|View full text |Cite
|
Sign up to set email alerts
|

Salting Effect on the Liquid−Liquid Equilibria for the Partially Miscible Systems of n-Propanol−Water and i-Propanol−Water

Abstract: The liquid-liquid equilibria (LLE) data were experimentally measured for the partially miscible systems of n-propanol-water-NaCl, n-propanol-water-NaBr, n-propanol-water-KCl, and i-propanol-water-NaCl at 25 °C. A method of calculation for the prediction of the salting effect on the LLE of organic aqueous solutions was proposed to correlate the experimental tie-line data. In the proposed method, the activity coefficients of the solvents were calculated by Tan's modified Wilson model which was combined with a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…The SOM acts as a separate material with very limited synergistic behavior with AS, namely with respect to the small decreases in the DRH and the ERH. These results are consistent with a model of phase separation between the organic and inorganic materials within a single particle, both in the presence and absence of water (Chou et al 1998;Marcolli and Krieger 2006;Ciobanu et al 2009). With respect to the arguments in favor of a biphasic particle, the weak effect of SOM on the ERH of water-containing particles is especially noteworthy.…”
Section: Discussionsupporting
confidence: 89%
“…The SOM acts as a separate material with very limited synergistic behavior with AS, namely with respect to the small decreases in the DRH and the ERH. These results are consistent with a model of phase separation between the organic and inorganic materials within a single particle, both in the presence and absence of water (Chou et al 1998;Marcolli and Krieger 2006;Ciobanu et al 2009). With respect to the arguments in favor of a biphasic particle, the weak effect of SOM on the ERH of water-containing particles is especially noteworthy.…”
Section: Discussionsupporting
confidence: 89%
“…41 Liquid-liquid equilibria measurements showed that the ternary mixtures NaCl/ n-propanol/water and NaCl/2-propanol/watersboth with OH/ CH n ratios of the alcohols of 1:3sexhibit a miscibility gap whereas the binary systems without the salt are completely miscible. 42,43 This behavior corresponds with the one of the NaCl/1,2-hexanediol/water system where the polyol also exhibits a OH/CH n ratio of 1:3. A reduced aqueous solubility of AS in the presence of the alcohol and a miscibility gap has also been observed for the system AS/2-propanol/water.…”
Section: Solubilities and Deliquescence Relative Humidities Ofmentioning
confidence: 55%
“…Up to now, various researchers were carrying out the study of ATPS by using a phase diagram in which they used some models and equations to correlate the binodal and tie line in liquid-liquid equilibria (LLE) [10][11][12][13][14][15][16]. In recent years, several researchers focused on the measurement and investigation of thermodynamics of ATPSs composed of an aqueous solution of a short chain aliphatic alcohol in the presence of an electrolyte [10,11,[17][18][19][20][21]. However, the detailed study of molecular interactions responsible for phase separation is not reported in detail.…”
Section: Introductionmentioning
confidence: 99%